Defense Response to Hemileia vastatrix in Susceptible Grafts onto Resistant Rootstock of Coffea arabica L. - Edgar Couttolenc-Brenis; Gloria Carrión; Luc Villain; Fernando Ortega-Escalona; Martín Mata-Rosas; Alfonso Méndez-Bravo (Agronomy, 2021)
The use of resistant cultivars and fungicides are common methods to control coffee leaf rust (CLR), the main disease that affects the Arabica coffee crop. In this study, we evaluated the response of grafted and ungrafted plants during the early stage of Hemileia vastatrix infection. We used ungrafted plants of Oro Azteca (resistant cultivar) and Garnica (susceptible cultivar), and grafted plants, combining both as rootstock and graft (Garnica/Oro Azteca and Oro Azteca/Garnica). All plants were inoculated with H. vastatrix uredospores, and we quantified the development of fungal structures in the leaf tissue of inoculated plants using qRT-PCR to measure relative expression of two pathogenesis recognition genes (CaNDR1 and CaNBS-LRR) and three genes associated with the salicylic acid (SA) pathway (CaNPR1, CaPR1 and CaPR5). In Garnica grafted on Oro Azteca, the fungal structures recorded were significantly less than in Garnica ungrafted plants. In addition, the expression of defense-related genes in grafted plants was higher than in ungrafted plants. Our results indicate that the defense response to CLR is strongly influenced by the rootstock employed.